Komunikasi Efektif VHF Channel 12 di Alur - Janny A. Djari; Arya Widiatmaja; Bayu Ardianto; Awal Mudzakir (Lembaga Penelitian dan Pengabdian Masyarakat, Akademi Maritim Nusantara Cilacap, 2023)
Effective communication is essential to prevent collision hazards or other hazards while navigating. VHF Radio is a communication tool that plays an essential role in communicating on board the ship. The Sampit shipping channel uses VHF radio Channel 12 as a pilot channel to assist the communication process when the boat moves in the channel. This study reviews the factors that impact effective communication using VHF Channel 12 radio and the effects caused by communication between ships or shore radio stations not going well. This study aimed to find out how to optimize the use of VHF Channel 12 radio as a pilot channel when the ship is maneuvering in the Sampit channel. The qualitative descriptive method refers to primary and secondary data collected previously, the research method used in this study. The data collected is in the form of articles, journals, news, and regulations related to the use of VHF Channel 12 radio when the ship is operating in the Sampit channel, as well as direct unstructured interviews with the Captain and Ship Officers and Pilots, to find out the factors that impede communication. In the Sampit channel and its impacts. After that, an analysis was conducted to optimize communication in the Sampit channel to assist the ship's maneuvering process. The conclusion obtained is that the provision of strict sanctions for vessels that use VHF Channel 12 as a Pilot channel services for other matters outside their designation is urgently needed to provide a deterrent effect and also training institutions that offer certification of expertise to provide more understanding to training participants regarding the designation function from the VHF Channel 12 as a Pilot Channel.